China’s Belt and Road Initiative Is Changing - Britta Kuhn (Wirtschaftsdienst)
Abstract Even before the coronavirus pandemic, financial and geopolitical problems were weighing on the “New Silk Road”: China’s overall investment has been declining for years, key construction projects are unprofitable, partners in Eastern and Southeastern Europe are turning away, and environmentally harmful projects are increasingly meeting resistance. Since 2020, affluent democracies reinforce alternatives and the People’s Republic also defers debt. In addition to the “BRI Green Partnership”, Xi Jinping is therefore pushing the “Digital Silk Road” and “China Standards 2035”, i. e. global technology and standardisation projects.